Peru – Progress in health and sciences in 200 years of independence - Carrillo-Larco, R.M.; Guzman-Vilca, W.C.; León-Velarde, F.; Bernabe-Ortiz, A.; Michelle Jiménez, M.M.; Penny, M.E.; Gianella Malca, C.; Leguia, M.; Tsukayama, P.; Hartinger, S.M.; Lescano, A.G.; Cuba-Fuentes, M.S.; et al. (Elsevier, 2022)
Peru celebrates 200 years of independence in 2021. Over this period of independent life, and despite the turbulent socio-political scenarios, from internal armed conflict to economic crisis to political instability over the last 40 years, Peru has experienced major changes on its epidemiological and population health profile. Major advancements in maternal and child health as well as in communicable diseases have been achieved in recent decades, and today Peru faces an increasing burden of non-communicable diseases including mental health conditions. In terms of the configuration of the public health system, Peru has also strived to secure country-wide optimal health care, struggling in particular to improve primary health care and intercultural services. The science and technology infrastructure has also evolved, although the need for substantial investments remains if advancing science is to be a national priority. Climate change will also bring significant challenges to population health given Peru's geographical and microclimates diversity. Looking back over the 200-years of independence, we present a summary of key advances in selected health-related fields, thus serving as the basis for reflections on pending agendas and future challenges, in order to look forward to ensuring the future health and wellbeing of the Peruvian population.
Keywords: Non-communicable diseases; Public health system; https://purl.org/pe-repo/ocde/ford#3.02.03